Haemodilution and head-down tilting induce functional injury in the rat optic nerve: A model for peri-operative ischemic optic neuropathy. Issue 11 (November 2018) - Roth, Steven; Dreixler, John; Newman, Nancy J.
Abstract : BACKGROUND: Mechanisms of peri-operative ischaemic optic neuropathy remain poorly understood. Both specific pre-operative and intra-operative factors have been examined by retrospective studies, but no animal model currently exists. OBJECTIVES: To develop a rodent model of peri-operative ischaemic optic neuropathy. In rats, we performed head-down tilt and/or haemodilution, theorising that the combination damages the optic nerve. DESIGN: Animal study. SETTING: Laboratory. ANIMALS: A total of 36 rats, in four groups, completed the functional examination of retina and optic nerve after the interventions. INTERVENTIONS: Anaesthetised groups ( n >8) were supine (SUP) for 5 h, head-down tilted 70° for 5 h, head-down tilted/haemodiluted for 5 h or SUP/haemodiluted for 5 h. We measured blood pressure, heart rate, intra-ocular pressure and maintained constant temperature. MAIN OUTCOME MEASUREMENTS: Retinal function (electroretinography), scotopic threshold response (STR) (for retinal ganglion cells) and visual evoked potentials (VEP) (for transmission through the optic nerve). We imaged the optic nerve in vivo and evaluated retinal histology, apoptotic cells and glial activation in the optic nerve. Retinal and optic nerve function were followed to 14 and 28 days after experiments. RESULTS: At 28 days in head down tilted/haemodiluted rats, negative STR decreased (about 50% amplitude reduction, P = 0.006), VEP wave N2-P3 decreased (70% amplitude reduction, P = 0.01) and P2 latency increased (35%, P = 0.003), optic discs were swollen and glial activation was present in the optic nerve. SUP/haemodiluted rats had decreases in negative STR and increased VEP latency, but no glial activation. CONCLUSION: An injury partly resembling human ischaemic optic neuropathy can be produced in rats by combining haemodilution and head-down tilt. Significant functional changes were also present with haemodilution alone. Future studies with this partial optic nerve injury may enable understanding of mechanisms of peri-operative ischaemic optic neuropathy and could help discover preventive or treatment strategies. Abstract : Supplemental Digital Content is available in the text